ENTREPRENEURIAL INTEREST IN SMK STUDENTS WITH GENDER AS A MODERATING VARIABLE - Liubana, Alfred; Kurjono (Jurnal Pendidikan Ilmu Sosial, 2024)
This study aims to analyze entrepreneurial interest in vocational students with gender as a moderating variable. According to Personality Theory, entrepreneurial interest can be predicted based on a person's personality traits. Entrepreneurial interest is essential for both male and female vocational students to prepare themselves for the future. Entrepreneurs have the potential to achieve financial success, build essential skills, and make a positive contribution to society. This research is quantitative. The population in this study is SMKN Kedawung, Jamblang and Susukan. The research data is primary data by distributing Likert scale questionnaires. The data analysis technique uses SEM_PLS to analyze data with the help of SmartPLS 3.0 software. The results of the study: Gender affects the interest in entrepreneurship, The need for achievement affects the interest in entrepreneurship, Locus of control affects the interest in entrepreneurship, Need for achievement on the interest in entrepreneurship with gender as moderation no effect and Locus of control on the interest in entrepreneurship with gender as moderation no effect.